Rhazes's Opinion about Relationship between Physical Activity and Eating Food - Mohammad Ebadiani; Marzieh-Beygom Siahpoosh; Alireza Nikbakht Nasrabadi; Gholamreza Shah Hosseini; Mohammad Mahdi Isfahani (Tehran University of Medical Sciences, 2017)
no abstract.